Neogene prehistory of the landscapes of Ukraine - Mykhailo Grodzynskyi (Kazimierz Wielki University, 2017)
The Neogene prehistory of the landscapes of Ukraine is considered as the first stage of the evolution of the modern landscapes. Its beginning is defined as the beginning of the late Miocene (Meotic age, 9,6 MA) and its end is correlated with the first Pleistocene glaciations on the Ukraine's territory. The degradation of Turgai forest flora (its criofitization and xerofitization) and increase of the area covered with the grass vegetation are the main factors of landscape genesis during their Neogene prehistory. Finally these changes have lead to the emergence of steppe zone in the southern Ukraine.